2018
DOI: 10.1371/journal.pone.0206622
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Streptococcus pneumoniae serotype 33F capsular polysaccharide locus that lacks wcjE and contains a wcyO pseudogene

Abstract: As part of large on-going vaccine impact studies in Fiji and Mongolia, we identified 25/2750 (0.9%) of nasopharyngeal swabs by microarray that were positive for Streptococcus pneumoniae contained pneumococci with a divergent 33F capsular polysaccharide locus (designated ‘33F-1’). We investigated the 33F-1 capsular polysaccharide locus to better understand the genetic variation and its potential impact on serotyping results. Whole genome sequencing was conducted on ten 33F-1 pneumococcal isolates. Initially, se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 30 publications
(38 reference statements)
2
13
0
Order By: Relevance
“…In total, 42/44 serotype 11X pneumococci were collected in Cambodia and Hong Kong, suggesting a primarily Asian or Pacific distribution, in line with the previous findings that pneumococci with this cps locus have previously been collected in Fiji, Thailand, Mongolia and Laos [19, 40]. The serotype 33X cps locus has recently been found (labelled as serotype variant 33F-1) in pneumococci isolated from healthy children and children with pneumonia in Fiji and Mongolia, respectively [38]. These studies along with the analysis conducted in this paper show that novel serotypes will continue to be discovered as more pneumococci from previously understudied regions are sequenced.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In total, 42/44 serotype 11X pneumococci were collected in Cambodia and Hong Kong, suggesting a primarily Asian or Pacific distribution, in line with the previous findings that pneumococci with this cps locus have previously been collected in Fiji, Thailand, Mongolia and Laos [19, 40]. The serotype 33X cps locus has recently been found (labelled as serotype variant 33F-1) in pneumococci isolated from healthy children and children with pneumonia in Fiji and Mongolia, respectively [38]. These studies along with the analysis conducted in this paper show that novel serotypes will continue to be discovered as more pneumococci from previously understudied regions are sequenced.…”
Section: Discussionsupporting
confidence: 76%
“…The presence of the functional glf in 18X1 suggests that galactofuranase may be present in the polysaccharide and absent in 18X2. The serotype 33C-like frameshifted wcyO in serotype 33X has been shown to mediate the same capsular modification as the serotype 33F wcjE [37, 38]. Two examples of wcjE or glf being replaced by transposons were observed in serotypes 9X and 18X3, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For 33F it was found that the isolates that gave an issue and caused an additional reference sequence to be necessary, had a missing gene wcjE , which had been replaced with wcyO in the capsular operon sequence. Variants similar to these had been noted in previous work [25]. It is highly likely that additional variants and representative capsular operon references will need to be added to the CTVdb, for other serogroups in stage 1 which demonstrated higher percentage of samples hitting with AMBER RAG status due to the initial hit being below 90 %.…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, Cao et al (2021) reported that while SeroBA predicted an isolate belonged to serogroup 24, subsequent testing with antisera specific to the group revealed that the isolate only reacted with 24D, not 24C or 24E, leading to its classification as serotype 24F. In a study by Manna et al (2018) , the 33F capsule locus sequence was analyzed using PneumoCaT, which identified a new clone of serotype 33F that contained a frameshift mutation, lacked wcjE , and had a wcyO pseudogene. In 2018, Kjeldsen et al (2018) employed a comprehensive approach comprising NMR spectroscopy, production of antisera, and serotyping using PneumoCaT, which enabled the identification of a novel serotype, 7D.…”
Section: Serotypingmentioning
confidence: 99%